Effect of Guanidine Hydrochloride on the Thermal Stability of Hen Egg White Lysozyme - Kumar, Sanjeev (My University, 2012)
The present work provides direct evidence that denaturant such as GdnHCl significantly affets the structure and thermal stability of lysozyme. In temperature induced unfolding of lysozyme, a thermal red-shift observed. In the present case, the GdnHCl dependence of unfolding free energy is linear over the full range of the denaturant concentration which suggests an absence of equilibrium intermediates in the U-> N folding of lysozyme also free energy change denaturant plot not deviates from LFEM, suggest an absence of equilibrium intermediate.
Keywords: Guanidine Hydrochloride; Hen Egg White Lysozyme; Thermal Stability; Thermodynamic parameters